Long-term growth comparison studies of FBS and FBS alternatives in six head and neck cell lines. - Chih-Yeu Fang (PLoS ONE, 2017)
Fetal bovine serum (FBS) is depended upon by investigators as an indispensable supplement in cell and tissue culture systems. Due to increased demand and limited availability, the price of FBS has increased by greater than 300% in the past few years. In addition, there are ethical and scientific controversies about the collection and use of FBS in culture systems. In response to the shortage of FBS, many FBS alternative serum products have been developed. Although many have claimed comparable performance to FBS, their support of long-term cell growth and effects on cell phenotype have not been revealed. In this study, we examined the performances of six bovine calf serum-based FBS alternatives in six head and neck cell lines and compared them with FBS. The results indicate that some of these sera had growth promoting capabilities comparable or superior to that of FBS. Additionally, these alternative sera supported long-term (30 passages) growth of tested cells and exhibited plating efficiencies comparable to that of FBS. Cells cultured in alternative sera also exhibited comparable anchorage-independent growth and similar drug inhibition responses in FBS. Still, caution should be taken in choosing suitable sera given that changes in cell morphology and variations in chemotactic responses were noted for cells maintained in certain sera. These FBS alternatives are more readily available, cost less, and are associated with less ethical concerns, thus making them attractive alternatives to FBS in cell culture systems.